Lower Postprandial Lipemia After Palmitic Acid-rich Fats with and Without Interesterification Is Associated with Increased Atherogenic Lipoproteins versus a High MUFA Oil (OR19-03-19). (13th June 2019) - Berry, Sarah; Mills, Charlotte; Harding, Scott; Bruce, Johanna; Gray, Robert; Bapir, Mariam; Roy, Caroline Le; Flottes, Laetitia; Lim, Delphine; Hall, Wendy
Abstract: Objectives: Interesterified (IE) fats are commonly used as hard fat alternatives to trans fats. However, their health effects are unknown. Postprandial lipemia is an independent risk factor for CVD; a prolonged postprandial lipemia may detrimentally impact lipoprotein remodelling. We compared the postprandial lipoprotein profiles of palmitic acid-rich IE and non-IE fats and an unsaturated control oil. Methods: A double blind, randomized controlled trial in healthy adults (n = 20) aged 45–75 years, assessed effects of single test meals (897 kcal, 50 g fat, 16 g protein, 88 g carbohydrate) on postprandial plasma triacylglycerol (TG) concentrations by colorimetric assay and lipoprotein profiles by NMR. Test fats were: a commonly consumed IE [80:20 palm stearin/palm kernel fat], the equivalent non-IE fat, and a control high-MUFA rich oil (canola oil, CO) as a reference point. Blood was collected at baseline, and hourly thereafter for 8h. Lipoprotein statistical analysis used linear mixed effect regression modelling (lme4 package on R). Metabolites were considered as response and treatment as predictor along with various covariates: time, period, baseline values, and subject (random effect), with post hoc adjustment for multiple comparisons. Results: There was a significant time x treatment interaction (P = 0.006) in change from baseline for plasma TG concentrations (Figure 1), with significant differences between the IE fat and CO and the non-IE fat and CO (both P = 0.001), but no difference between IE and non-IE fats. NMR analysis of lipoprotein (VLDL, HDL, LDL) particle size, composition and number, revealed an increase in particle and cholesterol concentrations following IE and non-IE fats versus the CO at T + 8h for the following lipoprotein fractions: chylomicron remnants and extremely large VLDL (non-IE vs CO P  < 0.05; IE vs CO P  < 0.001; Figure 2), and very large VLDL (non-IE vs CO P  < 0.01; IE vs CO P  < 0.005). Conclusions: Interesterification of a commonly consumed palm-based fat did not modify lipoprotein particle size or composition. Despite a reduction in postprandial lipemia, the generation of atherogenic TG-rich lipoprotein remnant particles in the late postprandial phase may in part explain the atherogenic potential of saturated rich fats compared with unsaturated rich fats. Funding Sources: BBSRC DRINC, UK. Supporting Tables, Images and/or Graphs: